Urine Protein-to-Creatinine Ratio Remains Informative Despite Nonsteady State Serum Creatinine During Acute Kidney Injury - Ian E. McCoy; Aris Oates; Chi-yuan Hsu (Kidney International Reports)
Introduction: Experts have cautioned that assessment of proteinuria using urine protein-to-creatinine ratios (UPCRs) are not valid during acute kidney injury (AKI) because reduced urine creatinine in the denominator may artificially inflate the ratio. However, there is little empiric data assessing this theoretical concern. Methods: Here, we retrospectively examined changes in UPCRs measured during episodes of severe AKI and assessed whether the magnitude and direction of these changes associate with how the serum creatinine level is changing at the time of UPCR collection. We repeated these analyses comparing hospitalization UPCRs with prehospitalization or posthospitalization UPCRs, where available. Results: Among 329 adults hospitalized with stage 2 or 3 AKI (defined as peak:nadir serum creatinine during hospitalization ≥ 2) at the University of California, San Francisco from January 1, 2014 to December 31, 2022 with multiple UPCRs measured during AKI hospitalization, UPCR values were similar whether the serum creatinine was increasing or decreasing at the time of measurement (median difference, 0.06 g/g; interquartile range [IQR], −0.26 to 0.50 g/g). There was no association between the difference in serum creatinine slopes when the UPCRs were collected and the difference in UPCR values (UPCR 0.05 g/g higher per mg/dl/d serum creatinine slope; 95% confidence interval [CI], −0.36 to 0.47, P = 0.80). UPCRs measured during hospitalization demonstrated positive and negative predictive values suggesting utility in appraising clinically relevant outpatient UPCR levels. Conclusion: Despite nonsteady state serum creatinine at the time of collection, UPCRs measured during AKI hospitalizations may be more informative than previously believed and should not be wholly disregarded.